2017
DOI: 10.3390/v9050098
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Local Immunity for an Effective Universal Swine Influenza Vaccine

Abstract: Influenza A virus infections are a global health threat to humans and are endemic in pigs, contributing to decreased weight gain and suboptimal reproductive performance. Pigs are also a source of new viruses of mixed swine, avian, and human origin, potentially capable of initiating human pandemics. Current inactivated vaccines induce neutralising antibody against the immunising strain but rapid escape occurs through antigenic drift of the surface glycoproteins. However, it is known that prior infection provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 117 publications
(144 reference statements)
0
13
0
Order By: Relevance
“…Adaptive immune responses of the lung are primarily initiated and maintained in bronchial and mediastinal lymph nodes that drain the lung but usually not within the lung tissue ( 3 ). Furthermore, following application of vaccines at peripheral sides such as skin or muscles, immune protection of the lung is limited ( 4 ).…”
Section: Bronchus-associated Lymphoid Tissue—baltmentioning
confidence: 99%
“…Adaptive immune responses of the lung are primarily initiated and maintained in bronchial and mediastinal lymph nodes that drain the lung but usually not within the lung tissue ( 3 ). Furthermore, following application of vaccines at peripheral sides such as skin or muscles, immune protection of the lung is limited ( 4 ).…”
Section: Bronchus-associated Lymphoid Tissue—baltmentioning
confidence: 99%
“…A long history of experiments in mice has also shown that T cells induced by live virus infection can protect in the absence of neutralizing antibody (13, 9598). In pigs the broadly protective vaccine candidate, signal minus Flu (S-FLU) reduced lung pathology and viral load in nasal swabs and the lung after homologous and partially matched challenge in the absence of neutralizing antibodies (99).…”
Section: T Cell Responses After Infection and Immunizationmentioning
confidence: 99%
“…Our hypothesis was that the immune system can be “tricked” to perceive cancer cells as influenza virus–infected cells following systemic delivery of virus-related antigens to targeted tumors and consequently launch an effective immune response against the cancer cells for treatment of metastatic disease. To test our hypothesis, we used influenza A virus–related antigens because influenza A virus is the most common cause of influenza virus infection in humans [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%